2012
DOI: 10.1002/j.1532-2149.2012.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of risk factors associated with transitioning from regional musculoskeletal pain to chronic widespread pain

Abstract: Chronic widespread pain has limited treatment options and is associated with pronounced negative individual and socioeconomic consequences. Patients with local or regional pain may be at a risk for developing chronic widespread pain. Knowledge of such risk factors can help prevent chronic widespread pain. This study systematically reviews the literature that examines risk factors associated with developing chronic widespread after developing chronic regional pain. We conducted a three-step database search in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 43 publications
7
60
3
2
Order By: Relevance
“…[34][35][36][37] Beyond that, female sex seems to be a risk factor for the onset of CWP among patients with CLBP. [9][10][11] The results of our study confi rm this assumption.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[34][35][36][37] Beyond that, female sex seems to be a risk factor for the onset of CWP among patients with CLBP. [9][10][11] The results of our study confi rm this assumption.…”
Section: Discussionsupporting
confidence: 83%
“…There are discrepancies to the systematic review by Larsson et al , 10 who reported an association of "age" and "depression" with pain generalization. However, apart from methodological limitations, none of the included studies investigated the infl uence of somatization, which may have confounded the association of depression and onset of CWP.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Compared to patients with a localized or regional chronic pain, CWP patients experience multiple pain sites and often experience high levels of anxiety and depression [14]. Although CWP often starts as a local or regional pain condition [15], the cause of the spreading of the pain remains unclear. Risk factors for CWP include female, higher age, depression, and family history of pain, but there is no clear consensus [15].…”
Section: Chronic Widespread Pain (Cwp) and Fibromyalgia (Fm)mentioning
confidence: 99%
“…Although CWP often starts as a local or regional pain condition [15], the cause of the spreading of the pain remains unclear. Risk factors for CWP include female, higher age, depression, and family history of pain, but there is no clear consensus [15]. Central and peripheral sensitization processes and defects in the inhibitory pain modulation pathways, as described above, could possibly explain the neurophysiological factors associated with CWP.…”
Section: Chronic Widespread Pain (Cwp) and Fibromyalgia (Fm)mentioning
confidence: 99%